Integrating and coordinating care between the Women, Infants, and Children Program and pediatricians to improve patient-centered preventive care for healthy growth. Issue 6 (23rd January 2018) - Bailey-Davis, Lisa; Kling, Samantha M R; Cochran, William J; Hassink, Sandra; Hess, Lindsey; Franceschelli Hosterman, Jennifer; Lutcher, Shawnee; Marini, Michele; Mowery, Jacob; Paul, Ian M; Savage, Jennifer S
Abstract: New care delivery models call for integrating health services to coordinate care and improve patient-centeredness. Such models have been embraced to coordinate care with evidence-based strategies to prevent obesity. Both the Special Supplemental Program for Women, Infants and Children (WIC) Program and pediatricians are considered credible sources of preventive guidance, and coordinating these independent siloes would benefit a vulnerable population. Using semistructured focus groups and interviews, we evaluated practices, messaging, and the prospect of integrating and coordinating care. Across Pennsylvania, WIC nutritionists ( n = 35), pediatricians ( n = 15), and parents ( N = 28) of an infant or toddler participated in 2016. Three themes were identified: health assessment data sharing (e.g., iron, growth measures), benefits and barriers to integrated health services, and coordinating care to reduce conflicting educational messages (e.g., breastfeeding, juice, introduction of solids). Stakeholders supported sharing health assessment data and integrating health services as strategies to enhance the quality of care, but were concerned about security and confidentiality. Overall, integrated, coordinated care was perceived to be an acceptable strategy to facilitate consistent, preventive education and improve patient-centeredness. Abstract : Pediatricians, WIC nutritionists, and parents perceive value in sharing health data across clinical and community settings to improve the quality of preventive counseling and care.